2018
DOI: 10.1111/cid.12613
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term prospective cohort study on immediately restored single tooth implants inserted in extraction sockets and healed ridges: CBCT analyses, soft tissue alterations, aesthetic ratings, and patient‐reported outcomes

Abstract: Substantial dimensional changes may be expected at the buccal aspect of single implants inserted in the premaxilla. As a result, contour augmentation procedures at the time of implant placement should be considered to counteract these bone alterations, even when implants are fully embedded in bone upon insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(94 citation statements)
references
References 30 publications
6
84
2
1
Order By: Relevance
“…Regarding the mid‐facial mucosal level compared with the contralateral tooth, a slight recession was observed at 12 months, without advanced mid‐facial recession (>1 mm). Similar findings have been reported by Cardaropoli et al, Raes et al, and Morimoto et al, while some other studies have also reported advanced recession (>1 mm) in a limited number of patients . Possible explanations for our data may be a stricter selection of patients with an intact buccal bone at implant placement, a thick gingival biotype, and a stringent surgical procedure.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding the mid‐facial mucosal level compared with the contralateral tooth, a slight recession was observed at 12 months, without advanced mid‐facial recession (>1 mm). Similar findings have been reported by Cardaropoli et al, Raes et al, and Morimoto et al, while some other studies have also reported advanced recession (>1 mm) in a limited number of patients . Possible explanations for our data may be a stricter selection of patients with an intact buccal bone at implant placement, a thick gingival biotype, and a stringent surgical procedure.…”
Section: Discussionsupporting
confidence: 91%
“…Immediate implant placement and provisionalization (IIPP) at the postextraction site in the esthetic zone has been shown to be a reliable therapy for patients and offers a reduced treatment time, high implant survival rate, and long‐term stability of marginal bone . The esthetic outcome of IIPP is dependent on the soft tissue contour .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groenendijk and colleagues reported in a 2‐year retrospective study on 16 patients a buccal bone thickness of 1.8 mm (varying from 0.9 to 2.4 mm). Raes and colleagues reported on a 8‐year prospective study with 16 patients with immediate placement. Median buccal bone thickness varied from 0.80 to 1.24 mm along the implant axis and never exceeded 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 24% of the cases were aesthetically inadequate (PES <8 and/or WES <6). Recently the 8-year aesthetic outcome of the same patient population was published with a mean PES-score of 10.4,45 indicating that the PES value, as scored after 1 year, remained stable after 8 to 10 years. Comparable studies, with long-term results on such a high number of patients treated with IIPP, are lacking.…”
mentioning
confidence: 96%